The economic theory of the location of railways an analysis of the conditions controlling the laying out of railways to effect the most judicious expenditure of capital - Wellington, A. M. 1847-1895 (John Wiley ; Engineering News ; Chapman & Hall, 1914)
In dealing with the economics of American railways the author considers: economic premises; the minor details of alignment; the importance of limiting gradients and curves; larger economic problems; the location of railway lines.
Includes index.
Keywords: Railroads -- Location.; Railroads -- Economics of construction.; elektronické knihy; electronic books